School-Based Assessment in Secondary School Science Learning: Teachers’ Perspective - Nwafor, Stephen Chinedu; Awosika, Opeyemi Fadekemi; Okoye, Grace Nwakaego (Indonesian Journal of Teaching in Science, 2024)
The study established the teachers' viewpoints on school-based assessment of secondary school science instruction in Anambra State, Nigeria. The research used a descriptive survey methodology. The 158 science teachers employed by the 32 public secondary schools in the Onitsha Education Zone of Anambra State made up the population of the study. Two of the three Local Government Areas of the Zone were chosen using the purposeful sampling technique, and the sample size was all 158 science teachers. "Questionnaire on Teachers Perception of the Use of Different Types of School Based Assessment in Teaching and Learning of Science in Secondary Schools" was a data collection tool created by researchers. It was validated, and Cronbach's alpha formula was used to determine its overall reliability, which was 0.71. For data analysis, mean and standard deviation were employed. According to the study's conclusions, science teachers in secondary schools use formative assessment in the teaching and learning of science courses to a moderate extent. Additionally, summative assessment is highly utilized in the teaching and learning of science subjects in secondary schools by science teachers, as opposed to diagnostic assessment, which is mostly underutilized (low extent). As a result, it was suggested, among other things, that science teachers be encouraged to utilize the many forms of school-based assessment for efficient science teaching and learning.